The Effect Of Consumption, Government Expenditure, Investment And Net Exports On Grdp Of Surabaya City - Erlangga Samudera Utomo; Parikesit Penangsang (Jurnal Multidisiplin Sahombu, 2024)
This study aims to analyze the effect of consumption, government spending, investment, and net exports on Gross Regional Domestic Product (GRDP) in Surabaya City for the period 2013-2023. The method used is multiple linear regression analysis with a descriptive approach, using secondary data. The results of the study indicate that consumption has a significant positive effect on GRDP with a t-value of 5.768 and sig 0.001, while government spending and investment do not show a significant effect on GRDP (sig 0.159 and 0.235, respectively). Net exports are recorded to have a significant positive effect with a t-value of 4.464 and sig 0.004. The F test shows that simultaneously, the four variables have a significant effect on GRDP with a sig value of 0.000. The conclusion of this study is that consumption and net exports have a greater contribution to GRDP growth in Surabaya City.